Impacts of Direct Cash Assistance, Social Security Enrollment, and Employment Stability on the Welfare of Hand-Rolled Cigarette Workers in Central Java - Calista, Maggie; Ahsan, Abdilah; Pertiwi, Yuyu (Jurnal Ketenagakerjaan, 2024)
This research investigates the relationship between Direct Cash Assistance (BLT) from the Tobacco Product Excise Profit Sharing Fund (DBHCHT), BPJS Employment, employment status, and the welfare of hand-rolled cigarette workers in Central Java, Indonesia. Given the significant shifts from manual to mechanized production in the tobacco industry, the study addresses the crucial aspect of worker welfare amidst these changes. The analysis focuses on four key areas: Pati, Kudus, Demak, and Jepara, utilizing data collected from 451 hand-rolled cigarette workers through structured interviews. The methodology involves an ordered logit regression model to evaluate how financial assistance, health and accident insurance coverage through BPJS Employment, and permanent versus contractual employment statuses impact the welfare of these workers, with welfare quantified in terms of income and asset ownership. The results indicate a positive correlation between the provision of BLT DBHCHT and improved welfare indices, highlighting the effectiveness of direct financial aid in enhancing living standards. Additionally, enrollment in BPJS Employment is significantly associated with better welfare outcomes, underscoring the importance of robust social security systems for protecting worker welfare. The study also finds that permanent employment contributes to higher welfare levels compared to contractual work, suggesting that job security plays a crucial role in promoting worker well-being. These findings underscore the necessity for targeted policy interventions aimed at improving socio-economic conditions for laborers within Indonesia's tobacco sector. They also advocate for an expanded scope of welfare indicators in future studies to include more comprehensive assessments of worker well-being, incorporating health, educational attainments, and psychosocial factors.